Estimativa da altura por dimensões dentárias: uma revisão da literatura - Herrera, Lara Maria [UNESP] (2014)
The knowledge of Forensic Anthropology is very importance in cases of identification of human remains. One phase of this process is the study of human height, which can be accomplished with relative ease when intact corpses, complete skeletons or long bones are available. However, the experience of Forensic Dentistry is essential in situations in which there is only information of the skull or of the teeth. The objective of this study was to review in the literature and evaluate works concerning the estimate of the height calculated from dental dimensions. Carrea, in 1920, proposed the estimation of the probable height of an individual by developing formulas for maximum and minimum heights from measurements of the lower central and lateral incisors and canines. The method was used in the case "Josef Mengele", to complement estimates. Tested in the Brazilian population, 70% of match between the actual and the estimated stature were obtained. Using more precise instruments, in the modified method, 96% of correct matching were verified. Recently, a new formula was introduced to estimate height, from measurements of upper teeth, because the technique cannot be used when jaw is not available. The correlation between height and dental dimensions is demonstrated. However, there is still a lack in scientific literature in this field, and further studies are necessary. The estimate of height from dental dimensions can be very useful and important, especially in situations where the complete skeleton it not found, and long bones are not available.